AB0164 ATG5 RS573755 is Protective of Erosive Damage Evaluated by Musculo-Skeletal Ultrasound in Patients with Systemic Lupus Erythematosus. (9th June 2015) - Perricone, C.; Iagnocco, A.; Ceccarelli, F.; Iorgoveanu, V.; Ciccacci, C.; Rufini, S.; Di Fusco, D.; Alessandri, C.; Spinelli, F.R.; Cipriano, E.; Novelli, G.; Valesini, G.; et al.
Abstract : Background: In the complex pathogenesis of Systemic Lupus Erythematosus (SLE), both genetic and environmental factors are involved possibly influencing the disease phenotype. Articular involvement is a frequent manifestation whose features range from arthralgia to erosive arthritis. Musculo-skeletal ultrasonography (MSUS) has proven useful in the assessment of inflammatory arthropathies and is more sensitive than radiography in detecting bone erosions. Objectives: We aimed at analyzing, in a population of Italian SLE patients, the relationship between 25 polymorphisms in 16 genes previously associated with SLE or other autoimmune diseases [1] and the presence of bone erosions observed by MSUS. Methods: Fifty-six consecutive SLE patients (M:F 3:53; mean age 41.5±10.0 years; mean disease duration 12.7±10.3 months) were enrolled. SLE diagnosis was performed according to the 1997 revised ACR criteria. Study protocol included complete physical examination and clinical and laboratory data collection. Twenty-five polymorphisms in 16 genes (STAT4, IL10, IL23R, IRAK1, PSORS1C1, HCP5, MIR146a, PTPN2, ERAP1, ATG16L1, IRGM, TRAF3IP2, VKORC1, CCR5, ATG5) were genotyped by allelic discrimination assays. Finally, bilateral high-resolution MSUS of the hand and foot joints was performed. The presence of erosive damage was assessed with a dichotomous score (absence/presence). Results: Forty-nine over 56 (87.5%) patients suffered from joint involvement in their clinical history. This clinical feature was associated with the presence of anti-Sm (P<0.05) but with none of the studied polymorphisms. The presence of erosions was demonstrated in 10/56 (17.8%) patients by MSUS. ATG5 rs573755 [P=0.026, OR=0.176 (95% CI: 0.034-0.922)] was protective of the development of erosions and a trend of a protective association was found for ATG5 rs2245214 [P=0.056, OR=0.251 (95% CI: 0.057-1.103)]. No other association was observed. Conclusions: Joint involvement, defined as per the 1997 revised ACR criteria, is a frequent manifestation in patients affected with SLE. However, the presence of bone erosions is far less common, may require a different management and may have a distinct pathogenesis. ATG5 is a possible candidate gene associated with disease susceptibility, and a key player in autophagy whose perturbations have been related with the development of SLE. Nonetheless, increased autophagy is an adaptive response to protect cells from stresses, and autophagy may regulate osteoarthritis-like gene expression changes, possibly protecting from the development of erosive damage. Since the clinical role of ATG5 in SLE may depend on other gene variants [2], its dichotomous behavior may not be surprising and deserves further investigation. References: Ciccacci C, Perricone C, Ceccarelli F, Rufini S, Di Fusco D, Alessandri C, Spinelli FR, Cipriano E, Novelli G, Valesini G, Borgiani P, Conti F. A multilocus genetic study in a cohort of Italian SLE patients confirms the association with STAT4 gene and describes a new association with HCP5 gene. PLoS One. 2014;9:e111991. Lόpez P, Alonso-Pérez E, Rodríguez-Carrio J, Suárez A. Influence of Atg5 mutation in SLE depends on functional IL-10 genotype. PLoS One. 2013;8:e78756. Disclosure of Interest: None declared